Respostas

  • Usuário do Brainly
2014-04-29T13:55:34-03:00
A(- 2, 3) e B(4, 1)

Encontrar o coeficiente angular, representado pela letra "m".

m = (y - y0)/x - x0
m = (1 - 3)/4 - (- 2)
m = - 2/4 + 2
m = - 2/6
m = - 1/3

y - y0 = m . (x - x0)
y - 3 = - 1/3 . (x - (- 2))
y - 3 = - 1/3 . (x + 2)
3 . (y - 3) = - 1 . (x + 2)
3y - 9 = - x - 2
- x - 2 = 3y - 9 (- 1)
x + 2 = - 3y + 9
x + 3y + 2 - 9 = 0
x + 3y - 7 = 0 (Equação geral da reta)

A(1, 3) e B(- 2, 4)

Encontrar o coeficiente angular, representado pela letra "m".

m = (y - y0)/x - x0
m = (4 - 3)/- 2 - 1
m = 1/- 3
m = - 1/3

y - y0 = m . (x - x0)
y - 3 = - 1/3 . (x - (- 1))
y - 3 = - 1/3 . (x + 1)
3 . (y - 3) = - 1 . (x + 1)
3y - 9 = - x - 1
- x - 1 = 3y - 9 (- 1)
x + 1 = - 3y + 9
x + 3y + 1 - 9 = 0
x + 3y - 8 = 0 (Equação geral da reta)